Phase Ia study of the indoleamine 2,3-dioxygenase 1 (IDO1) inhibitor navoximod (GDC-0919) in patients with recurrent advanced solid tumors - Asha Nayak-Kapoor; Zhonglin Hao; Ramses Sadek; Robin Dobbins; Lisa Marshall; Nicholas N. Vahanian; W. Jay Ramsey; Eugene Kennedy; Mario R. Mautino; Charles J. Link; Ray S. Lin; Stephanie Royer-Joo; et al. (Journal for ImmunoTherapy of Cancer, 2018)
Abstract Background Indoleamine-2,3-dioxygenase 1 (IDO1) catalyzes the oxidation of tryptophan into kynurenine and is partially responsible for acquired immune tolerance associated with cancer. The IDO1 small molecule inhibitor navoximod (GDC-0919, NLG-919) is active as a combination therapy in multiple tumor models. Methods This open-label Phase Ia study assessed safety, pharmacokinetics (PK), pharmacodynamics (PD), and preliminary anti-tumor activity of navoximod in patients with recurrent/advanced solid tumors, administered as 50-800 mg BID on a 21/28 day and at 600 mg on a 28/28 day schedule. Plasma kynurenine and tryptophan were longitudinally evaluated and tumor assessments were performed. Results Patients (n = 22) received a median of 3 cycles of navoximod. No maximum tolerated dose was reached. One dose-limiting toxicity of Grade 4 lower gastrointestinal hemorrhage was reported. Adverse events (AEs) regardless of causality in ≥20% of patients included fatigue (59%), cough, decreased appetite, and pruritus (41% each), nausea (36%), and vomiting (27%). Grade ≥ 3 AEs occurred in 14/22 patients (64%), and were related to navoximod in two patients (9%). Navoximod was rapidly absorbed (Tmax ~ 1 h) and exhibited dose-proportional increases in exposure, with a half-life (t1/2 ~ 11 h) supportive of BID dosing. Navoximod transiently decreased plasma kynurenine from baseline levels with kinetics consistent with its half-life. Of efficacy-evaluable patients, 8 (36%) had stable disease and 10 (46%) had progressive disease. Conclusions Navoximod was well-tolerated at doses up to 800 mg BID decreasing plasma kynurenine levels consistent with its half-life. Stable disease responses were observed. Trial registration ClinicalTrials.gov identifier: NCT02048709.